Quartz crystal elements and crystal devices

JP7630010B2Active Publication Date: 2025-02-14KYOCERA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023559885
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-15
Filing Date
2022-11-10
Publication Date
2025-02-14
Estimated Expiration
2042-11-10

Smart Images

  • Figure 0007630010000001
    Figure 0007630010000001
  • Figure 0007630010000002
    Figure 0007630010000002
  • Figure 0007630010000003
    Figure 0007630010000003
Patent Text Reader

Abstract

Provided are a crystal element and a crystal device that have a further improved drive level dependency (DLD) characteristic. The crystal element comprises a crystal piece (121), and a pair of electrodes (122a, 122b) positioned on both surfaces of the crystal piece (121) and including an electrically conductive layer with a gold content of 90% or more in mass ratio. In the crystal element, portions in which the DLD characteristic is in positive direction (+) and in opposite direction (-) are present in a mixed manner.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a quartz crystal element and a quartz crystal device. [Background technology]

[0002] It is known that a quartz crystal element that obtains a signal by resonating a quartz crystal piece at a predetermined frequency has a characteristic (DLD; Drive Level Dependency) in which the frequency increases as the drive level increases. JP 2020-25344 A discloses a technology for improving the structure and shape of electrodes in order to improve the DLD characteristic. Summary of the Invention [Means for solving the problem]

[0003] One aspect of the present disclosure is as follows. [A1] A crystal piece, A pair of electrodes having a conductive layer with a gold content of 90% or more by mass, the conductive layer being located on both sides of the crystal piece; A quartz crystal element comprising: A crystal element in which the DLD characteristics of the crystal element include a mixture of positive (+) and negative (-) parts. [A2] The quartz crystal element according to A1, further comprising an underlayer between the conductive layer and the quartz crystal blank. [A3] The quartz crystal element according to [A1] or [A2], wherein the resonant frequency of the quartz crystal element is 40 MHz or more and 400 MHz or less. [A4] The quartz crystal element according to any one of [A1] to [A3], wherein the thickness of the conductive layer of the quartz crystal element is 50 nm or more and 600 nm or less. [A5] The quartz crystal element according to any one of [A1] to [A4], wherein the quartz crystal element has a crystal impedance of less than 30 Ω. [A6] The quartz crystal element according to any one of [A1] to [A5], wherein the product of the thickness (mm) of the conductive layer and the resonant frequency (MHz) of the quartz crystal element is 0.017272 or more and 0.019684 or less. [A7] The quartz crystal element according to any one of [A1] to [A6], wherein the pair of electrodes are at the same position when viewed from above. [A8] A quartz crystal device comprising the quartz crystal element according to any one of [A1] to [A7]. Another aspect of the present disclosure is as follows. [B1] A crystal piece, Electrodes are provided on both sides of the crystal blank at the same position in a plan view, the electrodes having underlayers on both sides and conductive layers on the underlayers, the conductive layers having a gold content of 90% or more by mass; A quartz crystal element comprising: A quartz crystal element in which the product of the thickness (mm) of the conductive layer and the resonant frequency (MHz) of the quartz crystal element is 0.017272 or more and 0.019684 or less. [B2] The quartz crystal element according to [B1], wherein the value of the product is equal to or greater than 0.017933 and equal to or less than 0.018363. [B3] The quartz crystal element according to [B1] or [B2], wherein the resonant frequency is 76.8 MHz. [B4] A quartz crystal device comprising the quartz crystal element according to any one of [B1] to [B3]. [Brief description of the drawings]

[0004] [Figure 1] 2 is a diagram showing the shape of a cross section of the crystal device of the present embodiment. FIG. [Figure 2A] 1A and 1B are diagrams illustrating vibration of a quartz crystal element. [Figure 2B] 1A and 1B are diagrams illustrating vibration of a quartz crystal element. [Figure 2C] 1A and 1B are diagrams illustrating vibration of a quartz crystal element. [Diagram 3] 1 is a graph showing DLD characteristics according to the thickness of the excitation electrode when a target resonance frequency is specified. [Figure 4] FIG. 1 is a schematic diagram for explaining DLD characteristics. [Figure 5A] FIG. 11 is a graph showing a measurement example of DLD characteristics according to the thickness of the excitation electrode. [Figure 5B] FIG. 5B is an enlarged view of a portion of FIG. 5A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0005] Hereinafter, an embodiment will be described with reference to the drawings. FIG. 1 is a diagram showing the shape of a cross section of a crystal device 1 according to this embodiment. The crystal device 1 includes a base 11, a crystal vibration element 12 (crystal element), a conductive adhesive 13, a cover 14, a component 15, and the like.

[0006] The base 11 is not particularly limited, and may be, for example, a ceramic material, a crystal, a semiconductor material, a glass material, or a combination of these. The base 11 has a recess 11a in the center of the upper surface. An electrode pad 111 protruding from the bottom surface is located on the bottom surface of the recess 11a. The electrode pad 111 has a flat upper surface and may be formed by, for example, screen printing. The uppermost surface of the electrode pad 111 may be gold plated. The crystal vibration element 12 is bonded to the electrode pad 111 by a conductive adhesive 13. The conductive adhesive 13 may be, for example, a resin-based adhesive (for example, a silicone-based resin or an epoxy resin) containing a silver filler. In particular, the silicone-based resin conductive adhesive 13 is soft even after bonding, and is therefore unlikely to adversely affect vibration.

[0007] The quartz crystal vibrating element 12 includes a quartz crystal blank 121, a lower electrode 122a, an upper electrode 122b (collectively, excitation electrodes 122; electrodes), and a mounting electrode 124. The excitation electrodes 122 are in contact with both sides of the quartz crystal blank 121, sandwiching the vibrating portion of the quartz crystal blank 121 from above and below. The mounting electrode 124 is an electrode connected to an electric circuit in the base 11 via an electrode pad 111 in order to mount the quartz crystal vibrating element 12 on the base 11 and apply a voltage to the excitation electrode 122 from outside the quartz crystal vibrator 12, and is bonded with a conductive adhesive 13. As a result, the vibrating portion and the excitation electrode 122 are fixed in a floating state without contacting the inner wall surface of the recess 11a. The excitation electrode 122 and the mounting electrode 124 are a laminated structure of a base layer and a conductive layer located on the upper surface side of the base layer.

[0008] The underlayer plays a role in adhering the crystal blank 121 and the conductive layer. Such an underlayer is, for example, Cr, Ni, NiCr, Ti, or Mo. Of these, Cr is more preferable because it has a relatively low boiling point and can be formed on the crystal blank 121 at a relatively low temperature. The underlayer is, for example, 1 nm to 20 nm, and is preferably 10% or less of the thickness of the conductive layer. It is preferable that the underlayer is 1 nm or more because when the crystal unit 12 is affected by heat, the components of the underlayer diffuse into the conductive layer to suppress a decrease in adhesion of the conductive layer. On the other hand, it is preferable that the underlayer is 20 nm or less because it suppresses a decrease in electrical properties caused by the underlayer on the conductive layer.

[0009] There are no particular limitations on the conductive layer as long as it is made of a metal with high electrical conductivity. However, the density of the conductive layer, ρ (g cm -3 ) is preferably 15 or more and 25 or less, and particularly preferably 18 or more and 20 or less. Here, it is more preferable that the conductive layer is made of gold (Au). Here, gold means that the gold content is 90% or more by mass (impurities are less than 10%), preferably 95% or more, and particularly preferably 99% or more. Gold is preferable because it is chemically stable compared to other materials and does not easily react with oxygen or sulfur in the air, and as a result, it is less likely to cause a change in the frequency of the quartz crystal vibration element. The conductive layer may contain Ag, Al, or Cu. The conductive layer may be two or more layers.

[0010] The thickness of the conductive layer is usually 50 nm or more, preferably 75 nm or more, more preferably 100 nm or more, and particularly preferably 200 nm or more. The thickness of the conductive layer is usually 600 nm or less, more preferably 450 nm or less, and particularly preferably 300 nm or less.

[0011] The excitation electrode 122 and the mounting electrode 124 having such an underlayer and conductive layer may be formed by physical adsorption at a determined position using, for example, a sputtering device or a deposition device.

[0012] The crystal blank 121 has a substantially rectangular plate shape. The crystal blank 121 may be, for example, an AT cut, an SC cut, or a BT cut, and is preferably an AT cut. When the outer shape of the crystal blank 121 is formed by etching, residue may be generated on the side surface due to anisotropy of the etching. The corners of the crystal blank 121 may be rounded. The shape of the quartz crystal piece 121 is not particularly limited, but is preferably rectangular. The long side of the rectangular quartz crystal piece 121 is usually 300 μm to 1500 μm, preferably 500 μm to 1200 μm, and particularly preferably 700 μm to 1000 μm. The short side of the rectangular quartz crystal piece 121 is not particularly limited as long as it is shorter than the long side of the quartz crystal piece 121, but is usually 100 μm to 1100 μm, preferably 250 μm to 900 μm, and particularly preferably 400 μm to 700 μm. The ratio of the short side to the long side of the quartz crystal piece 121 is usually 0.07 to less than 1, preferably 0.25 to 0.9, and particularly preferably 0.5 to 0.8.

[0013] Thickness of crystal blank 121 T 1 is determined according to the resonance frequency of the quartz crystal element 12. T 1 does not have to be uniform throughout. As long as the thickness of the vibrating portion is specified as above, the portion surrounding the vibrating portion may be thicker / thinner, or only the portion of the mounting electrode 124 (one end side of the crystal blank 121) may be thicker.

[0014] The resonant frequency of the quartz crystal resonator element 12 is usually 40 MHz or more, preferably 45 MHz or more, more preferably 50 MHz or more, and even more preferably 75.8 MHz or more. The resonant frequency of the quartz crystal resonator 12 is usually 400 MHz or less, preferably 300 MHz or less, more preferably 200 MHz or less, even more preferably 150 MHz or less, particularly preferably 77.8 MHz or less, and particularly preferably 76.8 MHz.

[0015] The upper surface side of the recess 11a of the base 11, i.e., the upper end of the frame 112 surrounding the recess 11a, is joined to the lid 14 via a conductive sealing member such as gold-tin or silver solder, thereby sealing the recess 11a. A conductive frame-shaped metallized layer may be located between the base 11 and the lid 14.

[0016] The electrode pads 111 can be electrically connected to the outside via a signal line (not shown) that passes through the base 11 (for example, can be connected to an external wiring or substrate from an external connection pad located on the bottom surface of the base 11).

[0017] The component 15 is located on the bottom side of the base 11. The component 15 may be an electronic component such as an IC chip, or a sensor such as a temperature measuring element (such as a thermistor). The component 15 may also be a combination of a plurality of these. These output additional information related to the adjustment of the oscillation frequency of the crystal vibration element 12, or perform adjustment according to the additional information, that is, the crystal device 1 may be, for example, a temperature compensated crystal oscillator (TCXO). The position of the component 15 may not be near the center of the bottom surface in a plan view, but may be offset.

[0018] Next, the vibration of the quartz crystal vibration element 12 will be described. 2A to 2C are diagrams illustrating vibration of the quartz crystal vibration element 12. FIG. The crystal blank 121 of the crystal vibrating element 12 generates thickness-shear vibration in a plane perpendicular to the polarization direction, that is, along the extension direction of the crystal blank 121, due to polarization corresponding to the voltage applied between the upper electrode 122b and the lower electrode 122a. At this time, as shown in FIG. 2A, the excitation electrodes 122 are approximately rigid bodies and are simply weights located on the upper and lower surfaces of the crystal blank 121.

[0019] However, when the vibration frequency becomes high and the voltage, i.e., the drive level DL, becomes large, the electrodes can no longer be approximated as rigid bodies, and each electrode starts to vibrate elastically. In other words, an electrode material with a different elastic modulus from that of the quartz blank 121, in this case gold, is arranged in series with the quartz blank 121.

[0020] As shown in FIG. 2B, by driving with a high voltage in the high frequency band, the excitation electrode 122 may also vibrate in the same axial direction as the thickness-shear vibration direction of the crystal blank 121. In this case, as shown in FIG. 2C, the crystal blank 121, the lower electrode 122a, and the upper electrode 122b are connected in series to vibrate. That is, the combined spring constant k t is a combination of the spring constant k1 of the crystal blank 121 and the spring constant k2 of the excitation electrode 122, and is expressed by the following formula 1. k t =k1·k2 / (k1+k2) … (Formula 1)

[0021] In addition, the series spring of the crystal blank 121 and the excitation electrode 122 does not vibrate completely linearly due to the influence of the difference in their elastic modulus. In other words, as a nonlinear spring, for example, the vibration of the crystal blank 121 is expressed as follows: m k1 = Σ(i m u1 m ), and the vibration of the excitation electrode 122 is expressed as j n Then k2 = Σ(j n ·u2 n ) The coefficient i m , j n are values ​​determined by the quartz crystal blank 121 and the excitation electrode 122. Even in the case of a nonlinear spring, extremely high-order vibrations (for example, 4th to 7th orders or higher) can usually be ignored.

[0022] In addition, the actual quartz crystal vibrating element 12 has weight, and in particular, the weight of the gold of the excitation electrode 122 cannot be ignored, so here, the mass M as a weight is simply connected in series to the spring component. Note that the thickness of the underlayer of the excitation electrode 122 is sufficiently smaller (less than 10%) than the thickness of the conductive layer as described above, and its weight is also sufficiently small when the density ratio is taken into consideration, so that the effect on the characteristics of the excitation electrode 122 can be ignored. In the quartz crystal vibrating element 12, the contact area S between the quartz crystal blank 121 and the excitation electrode 122 is roughly determined by the resonance frequency F, so that under a certain material (i.e., density ρ is single), the mass M mainly depends on the thickness T2 of the excitation electrode 122. Here, the thickness T2 of the excitation electrode 122 refers to the average thickness of the conductive layer of the lower electrode 122a and the conductive layer of the upper electrode 122b.

[0023] The power (excitation level) that excites the vibration of the quartz crystal vibration element 12 is the average value of the power P applied to the quartz crystal vibration element 12. The amplitude u1 of the crystal blank 121 is determined by the series resistance R of the crystal vibrating element 12. / R) 1 / 2 (α is a proportionality constant). In other words, the amplitude u1 depends on the excitation level. The displacement velocity v1 and the displacement acceleration a1, which are the differential values ​​of the amplitude u1, depend on the resonance frequency F of the amplitude u1 in addition to the excitation level.

[0024] The displacement of the excitation electrode 122 is naturally the same as the displacement of the crystal blank 121 at the contact surface between the excitation electrode 122 and the crystal blank 121. At a position of the excitation electrode 122 away from the crystal blank 121, it is considered that a deformation occurs in the sliding direction (the same axial direction as the deformation direction of the crystal blank 121) that causes a delay in the displacement of the crystal blank 121 depending on the rigidity and inertia of the excitation electrode 122 (mass = gold density × contact area with the crystal blank 121 × thickness T2 perpendicular to the contact surface with the crystal blank 121, and the displacement acceleration a1 of the crystal blank 121). Therefore, the displacement (relative amplitude u2 with respect to the contact surface with the vibrating crystal blank 121) on the opposite side of the excitation electrode 122 from the side in contact with the crystal blank 121 is expressed by the following formula 2 depending on the thickness T2 of the excitation electrode 122 and the displacement acceleration a1 of the surface of the crystal blank 121 with respect to the displacement of the crystal blank 121. u2=T2·a1 / V2… (Formula 2) V2 is a constant that depends on the rigidity and mass, that is, on the material of the excitation electrode 122, and is the thickness shear sound velocity of the material. Therefore, the amplitude u2 depends on the excitation level and the resonance frequency F.

[0025] Here, as is well known, the resonant frequency F of the quartz vibration element 12 is expressed as v / λ, where v is the displacement speed and λ is the wavelength. The wavelength λ depends on the distance between the top and bottom surfaces of the quartz piece 121, which are the open ends of the vibration, i.e., the thickness T1 of the quartz piece 121. Therefore, the resonant frequency F is expressed by the following equation 3. F = (k t / M) 1 / 2 / (2πT1) … (Formula 3) As described above, the thickness T1 of the crystal blank 121 is a specified value according to the resonant frequency, and the mass M of the excitation electrode 122 depends on the thickness T2 of the excitation electrode 122. The combined nonlinear spring constant k t As described above, has a component that depends on the amplitude u1 of the crystal blank 121 and a component that depends on the amplitude u2 of the excitation electrode 122. From the above, the amplitude u1 depends on the excitation level, and the amplitude u2 depends on , Thickness The length T2 depends on the excitation level and the resonant frequency F.

[0026] If the excitation electrode 122 is a rigid body, the vibration depends only on the amplitude u1 of the former (quartz blank 121). In this case, as is conventionally known, the resonance frequency F of the quartz vibrating element 12 also changes (increases) monotonically (hardening spring) in accordance with the change (increase) in the excitation level. On the other hand, if the excitation electrode 122 also vibrates as described above, the resonance frequency F will change (increase) monotonically (hardening spring) in accordance with the change (increase) in the excitation level. u Since the product of each term depending on u2 and each term depending on the latter amplitude u2 is included, the resonance frequency F depends on the product of the resonance frequency F itself and the thickness T2 of the excitation electrode 122. In this case, whether the resonance frequency F increases monotonically in response to an increase in the excitation level depends on the coefficient of the high-order term of the spring constant kt related to the nonlinear vibration (thickness T 2 and the influence of the resonant frequency F) (mainly the magnitude of the coefficients of third-order or higher terms, etc.).

[0027] The ratio of the thickness T2 of the excitation electrode 122 to the thickness T1 of the crystal blank 121 is usually 0.0110 or more, and more preferably 0.0114 or more. This ratio is also usually 0.0138 or less, and more preferably 0.0124 or less. The ratio being in the above range is preferable because it improves the DLD characteristics. The excitation electrode 122 may be, for example, circular, elliptical, or polygonal in plan view, or a combination of parts thereof. The corners of the polygon of the excitation electrode 122 may be rounded. When the excitation electrode 122 is polygonal in plan view (including those with rounded corners), the polygon is preferably rectangular. In this case, the long side of the excitation electrode 122 is not particularly limited as long as it is shorter than the long side of the crystal piece 121, but is usually 100 μm to 1100 μm, preferably 250 μm to 900 μm, and particularly preferably 400 μm to 700 μm. The ratio of the long side of the excitation electrode 122 to the long side of the crystal piece 121 is usually 0.07 to less than 1, preferably 0.25 to 0.9, and particularly preferably 0.5 to 0.8. The ratio of the short side to the long side of the excitation electrode 122, which is rectangular in plan view, is usually 0.05 or more and less than 1, preferably 0.2 or more and 0.75 or less, and particularly preferably 0.3 or more and 0.5 or less. The shapes and sizes of the upper electrode 122b and the lower electrode 122a, which are components of the excitation electrode 122, may be the same or different from each other. The excitation electrodes 122 are preferably located at the same position in a plan view on both sides of the crystal piece 121. Here, the same position in a plan view means that, when the excitation electrode 122 is polygonal, each side of the upper electrode 122b and each side of the lower electrode 122a corresponding to each side are located within a range of ±5 μm from each other in a plan view.

[0028] FIG. 3 is a chart showing the tendency of change in resonance frequency F according to the thickness T2 of excitation electrode 122 in response to the excitation level when a target resonance frequency F (thickness T1 of crystal blank 121) is specified. This chart shows the thickness of each excitation electrode 122 when the set resonance frequency F is 76.8 MHz, the approximately rectangular crystal piece 121 (AT cut, thickness: 21.5 μm) has a long side of 805 μm and a short side of 537 μm, the excitation electrodes 122 (gold content: 99% or more) arranged on both sides of the crystal piece 121 have a long side of 559 μm and a short side of 233 μm, and the base layer between the crystal piece and the excitation electrode is made of chromium (Cr) and has a thickness of 4 nm. T The figure includes the measurement results when the excitation level was changed in the prototype of No. 2. Here, the dimensional tolerance of the excitation electrode 122 and the dimensional tolerance of the crystal blank 121 are each about ±10 μm.

[0029] The DLD characteristic (also called drive level dependency) indicates the increase or decrease in frequency change in response to a change in drive level. ΔF indicates the range of change in frequency in response to changes in the excitation level. Specifically, ΔF indicates the difference between the frequency corresponding to the excitation level and the frequency when the excitation level is 0.00 μW. In comparison with conventional products, when the excitation level (excitation power) is set to 250 μW, a ΔF of 0 ppm or more is preferable because spurious oscillation is less likely to occur, and a ΔF of 6 ppm or less is considered to be at a level that is practical and avoids malfunctions.

[0030] In the DLD characteristics, "-" indicates a tendency for the resonant frequency change range (ΔF) to monotonically decrease (reverse direction) as the excitation level increases when a graph (Y-axis (normal scale): ΔF, X-axis (logarithmic scale): excitation level) is created. Specifically, "-" means that the slope of ΔF and excitation level in the graph is less than 0. "+" indicates a tendency for ΔF to monotonically increase (positive direction) as the excitation level increases, and means that the slope of ΔF and excitation level in the graph is greater than 0. "±" indicates that there is a mixture of areas where the resonant frequency change range ΔF decreases (falls) and areas where it increases (rises) as the excitation level increases.

[0031] Specifically, the DLD characteristic according to the present disclosure is obtained by using a network analyzer to measure the change in the resonant frequency of the quartz crystal vibrating element 12 when the excitation level (also called excitation power) is changed from 0.01 to 250 μW. The presence of a mixture of "+" and "-" parts in the DLD characteristic is preferable in terms of stabilizing the frequency at start-up. It is preferable that the DLD characteristic is one in which ΔF varies with respect to the drive level according to a function of degree 3 or higher and takes at least a minimum value. More preferably, in the DLD characteristic, ΔF monotonically decreases from 0 to the minimum value. Even more preferably, in the "-" portion, the slope (Hz / μW) of the line connecting the measured value of ΔF at 0.01 μW in the graph to the minimum value is -20.0 or more. More preferably, this slope is -10.0 or more, and particularly preferably, the slope is -7.5 or more. Meanwhile, in the "+" portion, the slope (Hz / μW) of the line connecting the measured value of ΔF at 250 μW in the graph to the minimum value is 1.0×10 -1 It is preferable that the slope is 5.0×10 or less. More preferably, the slope is 5.0×10 -2 More preferably, the slope is 1.0×10 -2 The slope is preferably 5.0×10 or less. -3 The following is the result.

[0032] In addition, the crystal impedance (CI) is a value corresponding to the series equivalent resistance. It is determined that a CI of less than 30Ω is a level at which losses are acceptable for practical use. CI is preferably 25Ω or less, and more preferably 20Ω or less. There is no particular lower limit as long as it is greater than 0. The CI according to the present disclosure is specifically a network analyzer. - It is measured using

[0033] As can be seen from FIG. 3, the thickness of the excitation electrode 122 T When 2 is 224.9 nm or more, the forward direction (+) and reverse direction (-) are mixed in the DLD characteristics (Examples 1 to 5). 3 , Comparative Example 3 and Comparative Example 4 When this tendency is observed, the resonant frequency F, which initially changes in one direction as the excitation level increases, changes in the opposite direction halfway through, thereby canceling out the change, and the change in the resonant frequency F is suppressed over a wide range of excitation levels.

[0034] The film thickness (thickness) of the excitation electrode 122 T 2) is smaller than 200 nm (Comparative Example 1) and is larger than 300 nm, the influence of the secondary vibration becomes large, and the electrical characteristics of the crystal unit 12 deteriorate. In particular, when the long side of the crystal piece 121 is 1.2 mm or less, the primary vibration and the secondary vibration tend to couple easily, and the resonant frequency F changes abruptly. Therefore, the thickness of the excitation electrode 122 T If 2 is outside the range of 200 nm to 300 nm, suitable electrical characteristics cannot be obtained.

[0035] 4 is a schematic diagram for explaining the characteristic of the frequency change amount according to the drive level (DLD characteristic). When the frequency change amount ΔF is a linear or quadratic function with respect to the drive level, as shown by the dashed line, ΔF simply increases monotonically as the drive level increases, that is, the accuracy of the resonance frequency F simply decreases as the drive level increases. On the other hand, when ΔF is a cubic or higher function with respect to the drive level and has a maximum and a minimum, as shown by the solid line, ΔF does not monotonically increase (decrease) between the maximum and minimum or in a small range outside of the maximum and minimum (as long as it does not deviate significantly from this range), and a range in which the accuracy does not deteriorate significantly can be maintained.

[0036] Here, the thickness T When 2 is in the range of 233.5 nm or more and 239.1 nm or less (Examples 2 and 3), ΔF is 1.0 ppm or less, which is a much smaller range than usual (A). In other words, even if the excitation level is increased, the resonant frequency F does not change significantly, and practical problems are unlikely to occur.

[0037] However, the thickness of the excitation electrode 122 T If ΔF becomes even larger, the mass M of the excitation electrode 122 increases, and the effect as a weight becomes excessive, hindering the vibration of the crystal blank 121. As a result, the increase in CI becomes more noticeable than that of ΔF. T If 2 is 256.3 nm or less ( Comparative Example 3 ), which results in a CI of less than 30 Ω (B). T If 2 is further increased (Comparative Example 4 ), the CI becomes greater than 30 Ω, making it unsuitable for transmitting and receiving resonant frequency signals (C).

[0038] In other words, as described above, if the gold excitation electrode 122 is thick, resonance of the excitation electrode 122 will occur, and depending on the combination (product) of the spring constant associated with the resonance and the spring constant associated with the resonance of the quartz blank 121, it has been found that the change in resonance frequency F according to the excitation level tends to be suppressed over a wider range of excitation level changes than conventionally (the gold excitation electrode 122 acts as a softened spring and offsets the DLD characteristics associated with the vibration of the quartz blank 121).

[0039] In this way, in the crystal vibration element 12 having a resonance frequency in the high frequency band, here 76.8 MHz, the thickness of the excitation electrode 122 T By adjusting the thickness 2 to a larger value, it is possible to improve the DLD characteristics of the crystal blank 121. As described above, the only thing that can be changed other than the parameters related to the physical properties of the gold excitation electrode 122 and the crystal blank 121 is the thickness 2. T 2 and the resonant frequency F. Therefore, by keeping this value within an appropriate range, it is possible to improve the DLD characteristics of the quartz crystal vibrating element 12 while suppressing an increase in CI and the like as described above.

[0040] As mentioned above, when the resonant frequency F is 76.8 MHz, the thickness T 2 is less than 200 nm, i.e., the product value is less than 0.01536, and the thickness T When 2 is greater than 300 nm, that is, when the product is greater than 0.02304, the effects of secondary vibrations cannot be suppressed, and suitable electrical characteristics cannot be obtained. T Since the range of the thickness 2 is 224.9 nm or more and 256.3 nm or less, the range of the product of these is 0.017272 or more and 0.019684 or less (mm MHz). T Since 2 is between 233.5 nm and 239.1 nm, the range of the product is between 0.017933 and 0.018363 (mm MHz).

[0041] In addition, even if the frequency changes, the thickness T If 2 is changed, the same relationship as above is maintained. Considering the influence on the increase of CI, the above relationship can be applied when the resonance frequency F is in the range of several tens to several hundreds of MHz, particularly in the range of 40-400 MHz. In addition, the resonance frequency F=76.8 MHz may actually have a slight deviation (such as 1 to 2%).

[0042] FIG. 5A shows the thickness T 5B is a graph showing the measurement results of ΔF (Y axis: normal scale) versus excitation level (X axis: logarithmic scale) when ΔF2 is 102.0 nm (Comparative Example 1, white circles and solid line), 220.6 nm (Comparative Example 2, white squares and dashed line), and 233.5 nm (Example 2, black circles and dashed line). specific area This is an enlarged view.

[0043] Thickness T When thickness 2 is 102.0 nm and 220.6 nm, ΔF increases and decreases monotonically within the measurement range, respectively. T When 2 is 233.5 nm, the slope (Hz / μW) of the line connecting the measured value of 0.01 μW and the measured value at the minimum value in the graph in the "-" part is -5.05, while the slope of the line connecting the measured value at the minimum value in the graph and the measured value of 250 μW in the "+" part is 3.82 × 10 -3 It can be seen that by having the above-mentioned values ​​for the quartz crystal vibration element 12 in the "+" and "-" parts, it is possible to improve the DLD characteristics while suppressing increases in CI and the like.

[0044] As described above, the quartz crystal vibrating element 12 (quartz crystal element) of this embodiment includes the quartz crystal blank 121, and the excitation electrodes 122, which are located at the same position on both sides of the quartz crystal blank 121 in a plan view, and have underlayers located on both sides and a conductive layer located on the underlayers (i.e., sandwiched between the underlayer and the quartz crystal blank 121) and with a gold content of 90% or more by mass. The value of the product of the thickness (mm) of the excitation electrode 122 and the resonant frequency (MHz) of the quartz crystal vibrating element 12 is 0.017272 or more and 0.019684 or less. In the quartz crystal vibrating element 12, the thickness of the excitation electrode 122 with respect to the resonant frequency T By defining 2 in this way, the DLD characteristics can be improved and an appropriate resonant frequency F can be maintained even when the drive level is increased.

[0045] More preferably, the value of the above product is equal to or greater than 0.017933 and equal to or less than 0.018363. In this range, the DLD characteristics are sufficiently improved compared to the conventional case, and the CI can be kept at a small value, so that the quartz crystal vibrating element 12 can be vibrated efficiently relative to the power.

[0046] The resonant frequency F may be 76.8 MHz, which allows the CI and DLD characteristics to be adjusted to the optimum range.

[0047] The quartz crystal device 1 of this embodiment includes the above-mentioned quartz crystal vibrating element 12. According to this quartz crystal device 1, a stable resonant frequency F can be obtained over a wide range even when the drive level is changed, and therefore the quartz crystal device 1 can be stably used in electronic devices with a variety of drive levels.

[0048] The quartz crystal vibrating element 12 of this embodiment includes a quartz crystal blank 121 and a pair of electrodes 122a, 122b having conductive layers with a gold content of 90% or more by mass, which are located on both sides of the quartz crystal blank 121. The DLD characteristics of the quartz crystal element 12 include a mixture of positive (+) and negative (-) DLD characteristics. Therefore, the crystal vibration element 12 has improved DLD characteristics and is easily resonated near an appropriate frequency even when the drive level is changed. This stabilizes the frequency of the crystal vibration element 12 at startup.

[0049] Furthermore, the quartz crystal vibrating element 12 has a base layer between the conductive layer and the quartz crystal blank 121. This allows the electrodes 122a and 122b and the quartz crystal blank 121 in the quartz crystal vibrating element 12 to be reliably bonded to each other.

[0050] The resonant frequency of the quartz crystal vibrating element 12 is 40 MHz or more and 400 MHz or less. When the thickness of the quartz crystal blank 121 corresponds to such a resonant frequency band, the thickness of the electrodes 122a and 122b is set as described above. T By setting 2 in an appropriate range that is thicker than before, it is possible to stably improve the DLD characteristics.

[0051] In addition, the thickness of the conductive layer of the quartz crystal vibrating element 12 is 50 nm or more and 600 nm or less. By adjusting the thickness of the conductive layer of the electrodes 122a and 122b to be within this range, the DLD characteristics include a "+" part and a "-" part, and ΔF can be suppressed. Therefore, the DLD characteristics of this quartz crystal vibrating element 12 are improved.

[0052] Furthermore, the crystal impedance of the quartz crystal vibrating element 12 is less than 30Ω. By suppressing CI to a small value, the quartz crystal vibrating element 12 can be vibrated efficiently with low loss.

[0053] The above-described embodiment is merely an example, and various modifications are possible. For example, in the above embodiment, the crystal vibration element 12 that is a part of the crystal device 1 has been described, but this is not limiting. The crystal vibration element 12 may be manufactured, sold, or distributed as a single unit.

[0054] In the above embodiment, the appropriate thickness is determined by considering only the DLD characteristics and CI. T Although the range of 2 is considered, it is not limited to this range. Other parameters may also be considered. In addition, the specific configurations, materials, structures, etc. shown in the above embodiment can be appropriately changed without departing from the spirit of the present invention. The scope of the present invention includes the scope of the invention described in the claims and its equivalents. [Industrial Applicability]

[0055] The present disclosure can be applied to quartz elements and quartz devices.

Claims

1. A piece of crystal, A pair of electrodes are located on both sides of the crystal piece, the electrodes having conductive layers with a gold content of 90% or more by mass ratio; A quartz crystal element comprising: The DLD characteristics of the crystal element are a mixture of positive (+) and negative (-) parts, the value of the product of the thickness (mm) of the conductive layer and the resonant frequency (MHz) of the quartz crystal element is 0.017272 or more and 0.019684 or less; Quartz crystal element.

2. The quartz crystal element according to claim 1 , further comprising an underlayer between the conductive layer and the quartz crystal blank.

3. 2. The quartz crystal element according to claim 1, wherein the resonant frequency of the quartz crystal element is 40 MHz or more and 400 MHz or less.

4. The quartz crystal element according to claim 1 , wherein the conductive layer of the quartz crystal element has a thickness of 50 nm or more and 600 nm or less.

5. 2. The quartz crystal element of claim 1, wherein the quartz crystal element has a crystal impedance of less than 30 ohms.

6. The quartz crystal element according to claim 1 , wherein the pair of electrodes are at the same position when viewed from above.

7. A quartz crystal device comprising the quartz crystal element according to any one of claims 1 to 6.

8. A piece of crystal, An electrode is provided on each of both sides of the crystal blank at the same position in a plan view, the electrode having a base layer provided on each of the two sides and a conductive layer provided on the base layer and having a gold content of 90% or more by mass; A quartz crystal element comprising: The value of the product of the thickness (mm) of the conductive layer and the resonance frequency (MHz) of the quartz crystal element is 0.017272 or more and 0.019684 or less. Quartz crystal element.

9. The quartz crystal element according to claim 8 , wherein the value of the product is equal to or greater than 0.017933 and equal to or less than 0.018363.

10. The quartz crystal element according to claim 8 , wherein the resonant frequency is 76.8 MHz.

11. A quartz crystal device comprising the quartz crystal element according to any one of claims 8 to 10.

Citation Information

Patent Citations

  • Piezoelectric vibrating reed and its manufacture

    JP2001251160A

  • Crystal oscillating device and manufacturing method thereof

    JP2007096945A

  • Vibration element, vibrator, electronic device, electronic apparatus, mobile body, and manufacturing method of vibration element

    JP2013255052A

  • Vibration element, vibrator, electronic device, electronic apparatus, and mobile

    JP2014158149A

  • Piezoelectric vibration element, piezoelectric device using the piezoelectric vibration element, method of manufacturing piezoelectric vibration element, and method of manufacturing piezoelectric device using the piezoelectric vibration element

    JP2015109633A